2019
DOI: 10.1111/jvh.13227
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus pregenomic RNA status can reveal the long‐term prognoses of chronic hepatitis B patients treated with nucleos(t)ide analogues

Abstract: We examined whether the hepatitis B virus (HBV) pregenomic RNA (pgRNA) status after nucleos(t)ide (NA) treatment can predict the long‐time prognoses of chronic hepatitis B patients. Patients with chronic hepatitis B (98) who were treatment‐naïve and had begun a 7‐year NA therapy regimen were enrolled in this study. Biochemical indicators and serological markers of HBV infection were performed during therapy. HBV pgRNA was quantified by real‐time quantitative PCR with specific primers. During treatment, HBV DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 10 publications
2
28
2
Order By: Relevance
“…Plasma HBV RNA levels have been shown to predict response to pegylated interferon ( 8 , 11 , 23 ) and to NUC interruption ( 6 , 7 , 9 , 10 ): persons with suppressed plasma HBV DNA and RNA levels are less likely to develop HBV reactivation after NUC interruption than persons with suppressed HBV DNA levels but detectable HBV RNA levels. One potential explanation for this finding is that persons with suppressed HBV RNA levels might have infected cells that are transcriptionally inactive, and thus less likely to reactivate.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma HBV RNA levels have been shown to predict response to pegylated interferon ( 8 , 11 , 23 ) and to NUC interruption ( 6 , 7 , 9 , 10 ): persons with suppressed plasma HBV DNA and RNA levels are less likely to develop HBV reactivation after NUC interruption than persons with suppressed HBV DNA levels but detectable HBV RNA levels. One potential explanation for this finding is that persons with suppressed HBV RNA levels might have infected cells that are transcriptionally inactive, and thus less likely to reactivate.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, both serum HBV RNA and HBcrAg were reported to be potential surrogate biomarkers of cccDNA in predicting the outcomes of peg-IFN or NAs treatments [4,20,21]. The correlation of cccDNA with HBV RNA has also been studied before and after nucleos(t)ide analog treatment [5,21,22]. However, it is still unclear whether serum HBV RNA or HBcrAg is better as the surrogate marker of intrahepatic cccDNA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among the few patients experiencing significant HBV RNA declines during treatment with nucleo(s)tide analogues or PEG-IFN, HBV RNA decline was associated with higher rates of off-treatment sustained response. 18,20,21,24,33 Interestingly, two preliminary reports of recent studies in patients treated with novel capsid assembly modifiers have demonstrated superior HBV RNA declines. 13,25 Whether these declines also translate to higher rates of off- Until now, it has been unclear how such a response, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Recent studies suggest that a decline in serum HBV RNA levels during treatment with nucleo(s)tide analogues or PEG-IFN is associated with treatment response, although overall declines during treatment were limited. [19][20][21][22][23][24] Interestingly, recent phase 1 studies of novel capsid assembly modifiers have shown substantially stronger HBV RNA declines, which has been interpreted as a possible sign of a more potent effect on the intrahepatic HBV reservoir. 25 However, besides the observed decline in serum HBV RNA during capsid assembly modifiers therapy, little changes in hepatitis B surface antigen (HBsAg) and hepatitis B core-related antigen (HBcrAg) concentrations were observed in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation